Signal Recognition Particle RNA Contributes to Oxidative Stress Response in Deinococcus radiodurans by Modulating Catalase Localization - Han, Runhua; Fang, Jaden; Jiang, Jessie; Gaidamakova, Elena K.; Tkavc, Rok; Daly, Michael J.; Contreras, Lydia M. (Frontiers in Microbiology, 2020)
The proper functioning of many proteins requires their transport to the correct cellular compartment or their secretion. Signal recognition particle (SRP) is a major protein transport pathway responsible for the co-translational movement of integral membrane proteins as well as periplasmic proteins. Deinococcus radiodurans is a ubiquitous bacterium that expresses a complex phenotype of extreme oxidative stress resistance, which is mediated by proteins involved in DNA repair, metabolism, gene regulation and antioxidant defence. These proteins are located either extracellularly or subcellularly, but the molecular mechanism of protein localization in D. radiodurans to manage oxidative stress response remains unexplored. In this study, we characterized the SRP complex in D. radiodurans R1 and showed that the knockdown of the SRP RNA (Qpr6) reduced bacterial survival under hydrogen peroxide (H2O2) and growth under chronic ionizing radiation (CIR). Through LC-MS/MS analysis, we detected 162 proteins in the periplasm of wild-type D. radiodurans, of which the transport of 65 of these proteins to the periplasm was significantly reduced in the Qpr6 knockdown strain. By Western blotting, we further demonstrated the localization of the catalases in D. radiodurans, DR_1998 (KatE1) and DR_A0259 (KatE2), in both the cytoplasm and periplasm, and showed that the accumulation of KatE1 and KatE2 in the periplasm was reduced in the SRP-defective (Qpr6 knockdown) strain. Collectively, this study establishes the importance of the SRP pathway in survival and the transport of antioxidant proteins in D. radiodurans under oxidative stress.